Desain Logo Sebagai Identitas Visual Pondok Pesantren Baitul Hidayah - Ibrahim, Hasan (Fakultas Desain Universitas Komputer Indonesia, 2023)
Baitul Hidayah Islamic Boarding School is an Islamic educational institution that does not only focus on religious education, but also provides general education that can support community needs in facing challenges in social life in the future. it is evident from several findings in the field that there are inconsistencies in the application of logo identity in several media and also the minimal level of legibility in small media, because the identity of the Baitul Hidayah Islamic Boarding School is a representation of the values ​​shared by the people within the Institution and also a differentiator. If an educational institution does not apply its identity consistently, it will be difficult to demonstrate its existence. Therefore the Baitul Hidayah Islamic Boarding School needs a new identity in the form of a logo that can provide consistency for the media used and can also represent the values ​​shared by all human beings with the aim that the Baitul Hidayah Islamic Boarding School can be more consistent in applying identity to the media and other than The new logo will also give a fresh and more contemporary impression in line with current developments.